Kisah Hidup Nabi Muhammad: Teladan Bagi Umat Manusia - Muhammad rafly amriz; Muhammad zein abdillah; Andika Dwi Erdiansyah; Alviandy fitra Ritonga; Wismanto Wismanto; Fitria Mayasari (Institut Nalanda, 2024)
Background The life of the Prophet Muhammad SAW is based on a rich and profound story about a man who is an example for mankind. Muhammad was born in Mecca in 570 AD and grew up in a difficult environment, experiencing loss and hardship from an early age. However, his noble qualities such as honesty, wisdom, and compassion for others formed a strong personality and became the foundation of future leadership. As a prophet, Muhammad received revelations from Allah which later became the foundation of Islamic teachings. The purpose of this study is to explore and analyze important aspects of the life of the Prophet Muhammad and present examples that can be taken to be applied in everyday life. This type of research uses a qualitative approach, focusing on narrative analysis to understand the life story of the Prophet Muhammad and the values ​​contained therein. Data collected through analysis of various sources, namely the Qur'an and Hadith which include the teachings and actions of the Prophet Muhammad, biographical books, scientific articles, and other literature that discuss the life of the Prophet Muhammad and the socio-political context of his time. The results of this study are expected to provide a deep understanding of the example of the Prophet Muhammad and its relevance to mankind today.